2015
DOI: 10.3892/mmr.2015.4381
|View full text |Cite
|
Sign up to set email alerts
|

Orexin-A regulates cell apoptosis in human H295R adrenocortical cells via orexin receptor type 1 through the AKT signaling pathway

Abstract: Numerous studies have demonstrated the ability of orexin-A to regulate adrenocortical cells through the mitogen-activated protein kinase signaling pathway. In the present study, human H295R adrenocortical cells were exposed to orexin‑A (10‑10-10‑6 M), with orexin receptor type 1 (OX1 receptor) antagonist SB334867 or AKT antagonist PF‑04691502. It was found that orexin‑A stimulated H295R cell proliferation, reduced the pro‑apoptotic activity of caspase‑3 to protect against apoptotic cell death and increased cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“… 16 Orexin-A increases proliferation and decreases caspase-3 activity in H295R adrenocortical cells. 17 To the best of our knowledge, this study is the first to evaluate the neuroprotective effects of Orexin-A in H 2 O 2 -treated SH-SY5Y cells. The effects of increasing concentrations of Orexin-A on the H 2 O 2 -induced decrease in SH-SY5Y cell viability were evaluated.…”
Section: Discussionmentioning
confidence: 92%
“… 16 Orexin-A increases proliferation and decreases caspase-3 activity in H295R adrenocortical cells. 17 To the best of our knowledge, this study is the first to evaluate the neuroprotective effects of Orexin-A in H 2 O 2 -treated SH-SY5Y cells. The effects of increasing concentrations of Orexin-A on the H 2 O 2 -induced decrease in SH-SY5Y cell viability were evaluated.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, it was reported that orexin A increased the mRNA and protein expression levels of 3β-HSD and cortisol secretion by H295R cells in a dose-dependent manner, with 1 μM of orexin A showing the maximal effect. Of note, the effects were partly blocked by an OX1R antagonist [ 41 , 42 ]. These results suggest that orexin enhances a wide range of steroidogenic enzymes that are involved in the synthesis of mineralocorticoids and glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…Эта реакция выражена при применении орексина А в концентрации 1 мкМ. Аппликация орексина А приводила к усилению пролиферации клеток, выработки кортизола и увеличению экспрессии мРНК и белка 3-бета-гидроксистероиддегидрогеназы (3β-HSD) в клетках NCI-H295R; однако эти эффекты частично блокировались антагонистом рецептора OX1R [10].…”
Section: т 23 №unclassified